Analisis Hambatan Proses Lift Off Kontainer dari Kapal ke Truk Trailer Pada PT Samudera Sriwijaya Logistik di Palembang - Rizka Fadhilla (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
PT Samudera Sriwijaya Logistik is a subsidiary of PT Samudera Indonesia Tbk which is engaged in container loading and unloading services. Lift On or Lift Off is carried out at the container depot and at the shipyard or port. Lift On is a ship loading activity that raises containers from trailer trucks to ships and Lift Off is a ship unloading activity that lowers containers from ships to trailer trucks. trailers. Therefore the authors conducted interviews with operational parties to find out what obstacles occurred during the lift off process. Based on the results of the author's observations, the obstacles that occur when the lift off container process is caused by a lack of maintenance on the wirerope. This wirerope is a steel rope that is inside the wiredrum forming a circle and can make it easier for the wirerope to go in and out with the wirerope being neatly rolled up. There are problems related to this wirerope because there are wirerope that is broken, rusty, wirerope is not maintained, SOP is not working properly, officers forget to check wirerope, loading and unloading equipment data documents have errors and there is a load that exceeds capacity. These problems will be analyzed using fishbone diagrams or cause effect diagrams.